Do insects feel pain? A question at the intersection of animal behaviour, philosophy and robotics. (August 2016) - Adamo, Shelley Anne
Abstract : Insects are common model organisms for studies in animal behaviour, genetics, molecular biology and other fields. They are also the focus of pesticide research, a subspecialty devoted to devising chemicals capable of killing them. These studies would raise animal welfare concerns, if insects were thought capable of suffering (i.e. experiencing pain). Four disparate areas of research touch on the question of whether insects feel pain: (1) philosophy, (2) insect neurobiology and behaviour, (3) artificial intelligence and robotics and (4) evolution. Using the perspectives provided by these fields, I assess what we know about whether insects feel pain. Highlights: Neural/behavioural indicators of emotional components of pain in insects are unknown. I review four lines of evidence for pain experience in insects. Robots show more human 'pain-like' behaviour than insects. The evidence that insects experience pain is weak.